Blood glucose level affects prognosis of patients who received intravenous thrombolysis after acute ischemic stroke? A meta-analysis - Wang, Yue; Jiang, Guannan; Zhang, Jie; Wang, Jingfeng; You, Wanchun; Zhu, Juehua (Frontiers in Endocrinology, 2023)
Background and objectives: Intravenous recombinant tissue plasminogen activator (rtPA) thrombolysis is an effective treatment for actue ischemic stroke. Hyperglycemia is a major risk factor for the occurrence, development, and prognosis of ischemic stroke. This meta-analysis purposefully estimates the association between hyperglycemia and poor prognosis in acute ischemic stroke patients receiving intravenous rtPA thrombolytic therapy. Materials and methods: According to the predefined inclusion criteria, we searched PubMed, Web of Science, and Cochrane Library databases. The association of high blood glucose(>140mg/dl) with symptomatic intracranial hemorrhage (SICH), poor clinical outcome and mortality at 90 days post rtPA thrombolysis was studied using both a common effects model and a random effects model. Odds ratios (a ORs) were plotted on forest plots. Results: Of a total cohort of 2565 patients who received intravenous thrombolytic therapy, 721 had higher blood glucose. High glucose level significantly increased the odds of SICH (OR 1.80; 95% confidence interval(95%CI): 1.30- 2.50) and poor clinical outcome at 90 days (OR 1.82; 95%CI: 1.52-2.19), and all-cause mortality at 90 days (OR 2.51; 95%CI:1.65-3.82). Conclusions: In our meta-analysis, high blood glucose was significantly associated with SICH, poor clinical outcome and mortality at 90 days.